Assessing women participation in higher education leadership: case studies of Kenya, South Sudan, and Uganda - Mitullah , Winnie V.; Forojalla, Sibrino; Basheka, Benon; Vieira Do Nascimento, Daniele; Ginoyan, Karina (Revista Española de Educación Comparada, 2024)
Policy frameworks and legislation have enhanced the implementation of programs focused on improving women's education in Eastern Africa, yet gender parity remains a challenge in higher education, especially in top leadership positions. This study assesses women’s participation in leadership roles in higher education in Kenya, South Sudan, and Uganda and explores appointment criteria, obstacles, and mechanisms to increase female representation. Data were collected through desk research and a questionnaire aimed at university officials and administered online. The final sample consisted of 19 higher education institutions, and basic descriptive statistics were generated from the collected data. The results show that women comprise less than half of the top positions at both administrative and academic levels within the studied institutions. The key factors considered for appointing women to leadership positions include qualifications based on experience, leadership potential, and formal preparation. The study unveils challenges in the sector and contributes to evidence-based policymaking